Seeding Activity-Based Detection Uncovers the Different Release Mechanisms of Seed-Competent Tau Versus Inert Tau via Lysosomal Exocytosis - Tanaka, Yuki; Yamada, Kaoru; Satake, Kyoko; Nishida, Itaru; Heuberger, Matthias; Kuwahara, Tomoki; Iwatsubo, Takeshi (Frontiers in Neuroscience, 2019)
The pathological aggregation of tau characterizes a set of neurodegenerative diseases collectively referred to as tauopathies. Recent studies using cellular and animal models have suggested that tau pathology progresses by trans-cellular propagation. The process of propagation is mediated by certain species of extracellular tau, which are taken up by recipient cells and serve as a seed for tau aggregation. However, the molecular characteristics of extracellular seed-competent tau as well as its release mechanisms remain poorly investigated. Given that tau is physiologically released into the extracellular space, it is critical to distinguish seed-competent tau from normal monomeric tau. Utilizing biosensor cells expressing P301S mutant tau fused with CFP/YFP, here we discriminated between seed-competent tau and inert monomer tau released from HEK293 cells. By analyzing the size-exclusion fractions of the media, we found that seed-competent tau was enriched in high molecular weight fractions of ~2,000 kDa, while the majority of soluble tau positively detected by ELISA was in low molecular weight fractions. We also found that lysosomal stress induced by bafilomycin A1 or chloroquine increased Ca2+ dependent release of seed-competent tau without altering release of soluble tau. These data underscore the differential response of seed-competent tau and inert tau to lysosomal stress and indicates the presence of distinct release mechanisms.